Good governance in land tenure and administration (FAO RomeIT, 2007)
Explains what governance is, and what constitutes good governance in land tenure and administration. Examines the consequences of weak governance in these areas. Looks at how governance can be improved in land administration in general, as well as in some specific areas in which governance can be problematic.
Keywords: LAND TENURE